2022
DOI: 10.1177/02698811221142575
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clozapine treatment on the improvement of substance use disorders other than nicotine in individuals with schizophrenia spectrum disorders: A systematic review and meta-analysis

Abstract: Background: Antipsychotic medications are the mainstay of treatment for schizophrenia and are associated with a reduction in psychiatric hospitalization and overall mortality. Some evidence suggest that antipsychotic medications might have a varying effect on the improvement of comorbid substance use disorders (SUDs), with clozapine showing more favorable outcomes. Aim: We systematically reviewed all available evidence on effects of clozapine on the improvement of SUDs other than nicotine. Methods: Electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
1
10
0
1
Order By: Relevance
“…On the one hand, a feasible option is to provide LAI antipsychotics regimen as several evidence demonstrated it efficacy in treatment comorbid substance abuse in PLWS ( 78 80 ). On the other hand, meta-analytic evidence suggested that clozapine was superior to other AP in reducing substance misuse ( 81 ), while other findings observed that clozapine is strongly associated with reduced risk of developing substance use disorders among PLWS ( 82 ) maintaining them abstinent from misuse ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, a feasible option is to provide LAI antipsychotics regimen as several evidence demonstrated it efficacy in treatment comorbid substance abuse in PLWS ( 78 80 ). On the other hand, meta-analytic evidence suggested that clozapine was superior to other AP in reducing substance misuse ( 81 ), while other findings observed that clozapine is strongly associated with reduced risk of developing substance use disorders among PLWS ( 82 ) maintaining them abstinent from misuse ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies have indicated that atypical antipsychotics like clozapine, risperidone, and olanzapine have demonstrated effectiveness in managing psychotic symptoms and reducing substance use in individuals with DDs [ 22 , 23 , 24 , 25 , 26 ]. Specifically, according to recent studies, clozapine treatment is linked to markedly higher chances of maintaining abstinence from substance use and a reduced probability of psychiatric hospitalization in comparison to continued treatment with other antipsychotic medications [ 27 , 28 ]. This reduction in the intensity of craving could be mediated by the intrinsic characteristics of clozapine.…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic medications are the mainstay of treatment in SSD; yet, there is sparse research examining their impact on highly prevalent concurrent SUD outcomes. Some preliminary evidence, mainly from observational studies, have shown that clozapine is associated with more favorable effects on improving concurrent SUD outcomes compared with other antipsychotic medications ( Rafizadeh et al, 2022 ). There is, however, a dearth of evidence about its effects on outcomes related to concurrent MAUD in particular.…”
Section: Introductionmentioning
confidence: 99%